The cholinergic system modulates negative BOLD responses in the prefrontal cortex once electrical perforant pathway stimulation triggers neuronal afterdischarges in the hippocampus. Issue 2 (February 2022) - Arboit, Alberto; Krautwald, Karla; Angenstein, Frank
Repeated high-frequency pulse-burst stimulations of the rat perforant pathway elicited positive BOLD responses in the right hippocampus, septum and prefrontal cortex. However, when the first stimulation period also triggered neuronal afterdischarges in the hippocampus, then a delayed negative BOLD response in the prefrontal cortex was generated. While neuronal activity and cerebral blood volume (CBV) increased in the hippocampus during the period of hippocampal neuronal afterdischarges (h-nAD), CBV decreased in the prefrontal cortex, although neuronal activity did not decrease. Only after termination of h-nAD did CBV in the prefrontal cortex increase again. Thus, h-nAD triggered neuronal activity in the prefrontal cortex that counteracted the usual neuronal activity-related functional hyperemia. This process was significantly enhanced by pilocarpine, a mACh receptor agonist, and completely blocked when pilocarpine was co-administered with scopolamine, a mACh receptor antagonist. Scopolamine did not prevent the formation of the negative BOLD response, thus mACh receptors modulate the strength of the negative BOLD response.